2010
DOI: 10.4018/jcit.2010070106
|View full text |Cite
|
Sign up to set email alerts
|

Training in Technologically Enabled Environments

Abstract: The paper reports the findings from an experimental research study based on the pretest–posttest control group design, which examined the differential outcomes of spatial ability training attributed to training condition and gender. The study sample was comprised of 98 eighth graders (36 girls, 62 boys). The first experimental group (EG1) trained in interaction condition, the second experimental group (EG2) trained in animation condition, and the control group (CG) used printed materials. The groups underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Considering the control group had lower pre‐test accuracy on the paper folding task thus more room to improve, the results are encouraging that only the experimental group showed improvement. This is consistent with the findings of previous research that an interaction‐enabled virtual environment was useful in improving older adults' spatial abilities (Rafi et al, 2008), and supports the effectiveness of the 3D VFR stimuli. The results also align with the findings of Min and Chang (2022) that VFR attributes of garment patternmaking have the potential to enhance older adults' improvement scores and positively impacted their spatial visualization abilities.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Considering the control group had lower pre‐test accuracy on the paper folding task thus more room to improve, the results are encouraging that only the experimental group showed improvement. This is consistent with the findings of previous research that an interaction‐enabled virtual environment was useful in improving older adults' spatial abilities (Rafi et al, 2008), and supports the effectiveness of the 3D VFR stimuli. The results also align with the findings of Min and Chang (2022) that VFR attributes of garment patternmaking have the potential to enhance older adults' improvement scores and positively impacted their spatial visualization abilities.…”
Section: Discussionsupporting
confidence: 92%
“…The current study found that gender was not predictive of participants' improvement scores. Although previous findings have shown gender differences in the outcomes of spatial training, (e.g., Bruin et al, 2016; Feng et al, 2007; Rafi et al, 2008; Sherwin, 2003), men and women participants often differ in their spatial skills before training. When they were pair‐matched on spatial skills, thus men and women started with comparable pre‐test scores, their rate of learning did not differ (Spence et al, 2009).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The related literature displayed that, spatial visualization and mental rotation abilities have been measured with virtual environment and mostly real environment applications (Rafi et al, 2008;Uygan, 2011). However, in the literature, studies have been made with real environments and objects related to robotics and Lego Mindstorms.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%